Investigation of the Enteric Pathogenic Potential of Oral Campylobacter concisus Strains Isolated from Patients with Inflammatory Bowel Disease - Ismail, Yazan (Public Library of Science, 2012)
BACKGROUND: Campylobacter concisus, a bacterium colonizing the human oral cavity, has been shown to be associated with inflammatory bowel disease (IBD). This study investigated if patients with IBD are colonized with specific oral C. concisus strains that have potential to cause enteric diseases. METHODOLOGY: Seventy oral and enteric C. concisus isolates obtained from eight patients with IBD and six controls were examined for housekeeping genes by multilocus sequence typing (MLST), Caco2 cell invasion by gentamicin-protection-assay, protein analysis by mass spectrometry and SDS-PAGE, and morphology by scanning electron microscopy. The whole genome sequenced C. concisus strain 13826 which was isolated from an individual with bloody diarrhea was included in MLST analysis. PRINCIPAL FINDINGS: MLST analysis showed that 87.5% of individuals whose C. concisus belonged to Cluster I had inflammatory enteric diseases (six IBD and one with bloody diarrhea), which was significantly higher than that in the remaining individuals (28.6%) (P<0.05). Enteric invasive C. concisus (EICC) oral strain was detected in 50% of patients with IBD and none of the controls. All EICC strains were in Cluster 1. The C. concisus strain colonizing intestinal tissues of patient No. 1 was closely related to the oral C. concisus strain from patient No. 6 and had gene recombination with the patient’s own oral C. concisus. The oral and intestinal C. concisus strains of patient No. 3 were the same strain. Some individuals were colonized with multiple oral C. concisus strains that have undergone natural recombination. CONCLUSIONS: This study provides the first evidence that patients with IBD are colonized with specific oral C. concisus strains, with some being EICC strains. C. concisus colonizing intestinal tissues of patients with IBD at least in some instances results from an endogenous colonization of the patient’s oral C. concisus and that C. concisus strains undergo natural recombination.